Measuring the performance of image data by using RLE algorithm in lossless compression technique - Nurmarsyita, Mohd Shah (2015)
Lossless compression technique for measuring the performance of image data is a technique that build for reduce the size of image but still will produce the high quality of image data. There are a lot of lossless compression technique that can measure the performance of image data which are Huffman, Arithmetic, Lempel-Ziv Welch (LZW) and Run-Length Encoding (RLE) . In the research, there are one technique that will selected for this problem which is Run-Length Encoding algorithm. From this technique, it will be develop the high quality of data by reducing the size of image but give a high quality of image. This result will produce by using lossless compression technique which is consist of four stage such as analysis, pre-processing, design, probability algorithm and testing.